Study of tube-shell heat exchangers fouling problem - Chaima Aouissi; Habchi, Safaa; Abdelmouiz, Ahmed (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2023)
The study carried out on the Tube-Shell exchanger P30-GA-21-01 A/B shows that it encounters problems which are manifested by the presence of additional resistors and an increase in pressure drops. This change results in the inability to ensure heat exchange. This study makes it possible to optimize the current operating parameters and compare it with those of design cases, thus estimating the various possible methods to eliminate the fouling of the tubes to improve the efficiency of the heat exchanger. This study makes it possible to optimize the current operating parameters and compare it with those of design cases, thus estimating the various possible methods to eliminate the fouling of the tubes to improve the efficiency of the heat exchanger.
Option : Chemical engineering